Attitudes of MBBS students towards medical profession: A study in a medical school - Kasarla, Rajeshwar Reddy; Verma, Aishwarya; Pathak, Laxmi (Janaki Medical College Journal of Medical Science, 2022)
Background and Objectives: The professional attitude of the Doctor is mainly concerned with his/her feelings, beliefs and behavior towards the patients. The students are admitted to MBBS through a written test (entrance test) in three subjects’ viz. Physics, Chemistry, and Biology to qualify for the admission. But, no test is conducted to evaluate the attitudes of students, who seek admission into medical colleges. Hence, this study was undertaken to evaluate the attitudes of medical students i.e., whether they have right/positive attitude for the medical profession. Material and Methods: A descriptive, cross-sectional study was carried out on 100 MBBS students of 4th and 5th year of Universal College of Medical Sciences, Bhairahawa, Nepal by administering a questionnaire constructed on the lines of Likert’s summated rating scale to measure the attitudes of MBBS students towards medical profession. The tool consisted 32 statements, both positive as well as negative. Each statement had four alternative responses against it, namely – Strongly Agree (SA), Agree (A), Disagree (DA), and Strongly Disagree (SD). The questionnaire in Google form was mailed to all students. The students were asked to read each statement carefully and click on their opinion/response. Results: This study revealed that the gender, parents’ occupational background, and socio-economic status influences the attitudes of 4th and 5th year MBBS students and differ significantly towards their medical profession. Whereas age, locality, and nationality were not influencing factors for the attitudes 4th and 5th year MBBS students towards their medical profession. Conclusion: The present study on attitudes of MBBS students towards medical profession has several important implications for medical education. The findings of present study could be helpful to the planners, policy makers of medical education, so as to bring changes in entrance test for admission into MBBS course, and helpful to medical colleges and medical teachers so that they can conduct counselling and guidance programs so as to promote a positive attitude among medical students towards medical profession. Research literature of this type will serve as a self-instructional material for MBBS students to understand their medical profession in a scientific manner.